Intrasellar Rathke’s Cleft Cyst and Acromegaly: an Unusual Coincidence - Efstathiadou, Z. A.; Poulasouchidou, M. K.; Zouli, C.; Anastasiou, A.; Kita, M. D. (Experimental and Clinical Endocrinology & Diabetes Reports, 2015)
The concomitant presence of 2 histologically different pituitary lesions is relatively uncommon. Cases of coexistent growth hormone (GH) secreting pituitary adenomas and Rathke’s cleft cysts are limited to 14. The preoperative clinical and radiological features of dual sellar lesions are variable and diagnosis is usually confirmed only by histology. We describe a case of a GH-secreting pituitary adenoma complicated by the presence of an asymptomatic intrasellar Rathke’s cleft cyst and review the already reported cases.
Keywords: somatotroph adenoma; acromegaly; Rathke’s cleft cyst; growth hormone; pituitary adenoma